2014
DOI: 10.3171/2014.1.spine13426
|View full text |Cite
|
Sign up to set email alerts
|

Load sharing in lumbar spinal segment as a function of location of center of rotation

Abstract: Object The center (axis) of rotation (COR) in the lumbar spine has been studied well. However, there is limited information on the kinetic and kinematic consequences of imposed shift in the location of the COR, although this type of shift can be seen after surgeries using motion preservation or dynamic stabilization devices. The objective of this study was to assess the kinetic and kinematic changes in the lumbar spinal segment due to various imposed CORs. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…It has been reported that the alternation of lumbar COR could cause considerable changes in muscle forces using a musculoskeletal model [10]. In addition, the finite element analysis has also shown that the facet forces, ligament loads, and disc stresses are strongly correlated with the location of COR [11]. In an in vitro study, it was found that the higher position of COR correlated with the lower facet force [12].…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that the alternation of lumbar COR could cause considerable changes in muscle forces using a musculoskeletal model [10]. In addition, the finite element analysis has also shown that the facet forces, ligament loads, and disc stresses are strongly correlated with the location of COR [11]. In an in vitro study, it was found that the higher position of COR correlated with the lower facet force [12].…”
Section: Introductionmentioning
confidence: 98%
“…The lumbar spine's load-bearing area lies largely within its anterior column throughout most of its range of movement [6] and can be represented by changes in relative disk heights across the endplates [7,8]. In this study, we aimed to identify the load-bearing pattern of each functional spinal unit (FSU) using the changes in relative disk heights that occur during commonly assumed, clinically meaningful physiological postures: flexion (slump sitting), erect (standing), and extension (backward bending).…”
Section: Introductionmentioning
confidence: 99%
“…The kinematics and kinetics of the lumbar spine may be sensitive to the location and radius of the COR. Alapan et al [12] constructed and validated a 3D finite element model of an L4–L5 unit and then assessed the kinematic and kinetic changes in the lumbar spine in different COR positions. They found that ROM, facet forces, ligament loads, and disc stresses were strongly correlated with the location of the COR.…”
Section: Introductionmentioning
confidence: 99%